Expansion and further delineation of the SETD5 phenotype leading to global developmental delay, variable dysmorphic features, and reduced penetrance. Issue 4 (7th January 2018) - Powis, Z.; Farwell Hagman, K.D.; Mroske, C.; McWalter, K.; Cohen, J.S.; Colombo, R.; Serretti, A.; Fatemi, A.; David, K.L.; Reynolds, J.; Immken, L.; Nagakura, H.; et al.
Abstract : Diagnostic exome sequencing (DES) has aided delineation of the phenotypic spectrum of rare genetic etiologies of intellectual disability (ID). A SET domain containing 5 gene ( SETD5 ) phenotype of ID and dysmorphic features has been previously described in relation to patients with 3p25.3 deletions and in a few individuals with de novo sequence alterations. Herein, we present additional patients with pathogenic SETD5 sequence alterations. The majority of patients in this cohort and previously reported have developmental delay, behavioral/psychiatric issues, and variable hand and skeletal abnormalities. We also present an apparently unaffected carrier mother of an affected individual and a carrier mother with normal intelligence and affected twin sons. We suggest that the phenotype of SETD5 is more complex and variable than previously presented. Therefore, many features and presentations need to be considered when evaluating a patient for SETD5 alterations through DES. Abstract : Case series and review of literature of patients with pathogenic SETD5 alterations. Phenotype is variable but encompasses developmental delay, behavioral/psychiatric issues, and variable hand and skeletal abnormalities and highly variable dysmorphic features.